English After RP Standard British Pronunciation Today - Lindsey, Geoff; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book concisely describes ways in which today's standard British English speech differs from the upper-class accent of the last century, Received Pronunciation, which many now find old-fashioned or even comic. In doing so it provides a much-needed update to the existing RP-based descriptions by which the sound system of British English is still known to many around the world. The book opens with an account of the rise and fall of RP, before turning to a systematic analysis of the phonetic developments between RP and contemporary Standard Southern British (SSB) in vowels, consonants, stress, connected speech and intonation. Topics covered include the anti-clockwise vowel shift, the use of glottal stops, 'intrusive r', vocal fry and Uptalk. It concludes with a Mini Dictionary of well over 100 words illustrating the changes described throughout the book, and provides a chart of updated IPA vowel symbols. This book is an essentialresource for anyone interested in British pronunciation and sound change, including academics in phonetics, phonology, applied linguistics and English language; trainers of English teachers; English teachers themselves; teachers of voice and accent coaches; and students in those areas.
Introduction: What was RP? -- Part I. Changes: General observations -- Chapter 1. The power of writing -- Chapter 2. The special relationship -- Chapter 3. Getting stronger -- Part II. Vowels -- Chapter 4. The anti-clockwise vowel shift -- Chapter 5. FLEECE, GOOSE and other diphthongs -- Chapter 6. GOAT, GOOSE and FOOT backing -- Chapter 7. A LOT more common -- Chapter 8. KIT - still going strong (but happY never existed) -- Chapter 9. FOOT - even rarer, but still common! -- Chapter 10. Weak vowel merger -- Chapter 11. Two kinds of BATH -- Chapter 12. PRICE and MOUTH -- Chapter 13. The decline of the centring diphthongs -- Part III. Consonants -- Chapter 14. More aspiration (and affrication) -- Chapter 15. /tʃ/ and /dʒ/ - a new si-chew-ation -- Chapter 16. /tʃ/ and /dʒ/ - a new chrend -- Chapter 17. Epen-t-thesis -- Chapter 18. Syllabic consonants - a little less certain -- Chapter 19. Glottal stops, part 1 -- Chapter 20. Is /l/ following /r/? -- Chapter 21. G-dropping and H-dropping -- Chapter 22. Fings to come? -- Part IV. Stress -- Chapter 23. The love of alternating stress -- Chapter 24. Westwards toward America? -- Part V. Connected speech -- Chapter 25. Linking /r/ -- Chapter 26. Glottal stops, part 2 -- Chapter 27. Vocal fry -- Part VI. Intonation -- Chapter 28. Falls -- Chapter 29. Yes-no questions -- Chapter 30. Continuation patterns -- Chapter 31. Uptalk -- Part VII. Mini Dictionary.
Keywords: Linguistics; Germanic languages; Grammar, Comparative and general -- Phonology; Sociolinguistics; Linguistic change; Language and languages -- Study and teaching; Linguistics; Germanic Languages; Phonology and Phonetics; Sociolinguistics; Language Change; Language Teaching and Learning